Rapid FDI expansion and firm performance - Chang, Sea-Jin; Rhee, Jay Hyuk (Journal of International Business Studies, 2011)
Today, more firms are expanding rapidly into foreign markets to reach global scale quickly, and to capture or nullify first-mover advantages. These trends run counter to the conventional theory of gradual internationalization, which suggests that firms maximize the benefits of learning from prior experience, thereby minimizing the hazard of failure. We argue that this conventional wisdom does not consider the risk of being a perennial late mover in the face of increased global competition. This study explores the circumstances under which rapid FDI expansion, a strategy of undertaking FDI expansion at an accelerated speed, can be a viable strategy. Using data on Korean firm expansion, we find that rapid FDI expansion enhances firm performance in industries where globalization pressures are high, and when it is done by firms with superior internal resources and capabilities.